Understanding Prosperity and Poverty in Why Nations Fail; The Origins of Power, Prosperity, and Poverty: A Book Review - Anyim-Ben, Francisca; Anyim, Anyim Benjamin; Anyim, Annastecia Ngozi (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2018)
Chapter fifteen of the book Why Nations Fail by Acemoglu and Robinson titled Prosperity and Poverty is the last and summarizing chapter of the masterpiece. The work undertook an intellectual and rigorous journey to logically and coherently expose the causes of obvious inequality amongst nations of the world. The chapter has its central message that the extractive economic and political institutions are hypothetically the reason why some countries are poor; the study highlighted the features of extractive institutions to include: quick economic growth, inherent fighting, systematic disorder, and elite domination. The work is an attempt to comprehensively review and bring to bear an in-depth understanding of prosperity and poverty amongst nations of the world. It, therefore, states that to move into prosperity, poor nations have to create and develop a more inclusive economic and political institution. Thus; the review concluded that poor countries of the world need strong inclusive institutions to leapfrog into prosperity.